Perbedaan Hasil Pemeriksaan Kolesterol Total dalam Darah Menggunakan Alat Architect C4000 dan Alinity C1000 - Retno Rusnaini; Nyoman Sudarma; Ni Luh Gede Puspita Yanti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Total cholesterol measurement is essential for assessing cardiovascular risk, but consistency between laboratory instruments must be validated for reliable results. Architect C4000 and Alinity C1000 operate on enzymatic principles but differ in system design, reagents, and supporting technology. This study aimed to compare total cholesterol measurements between the two instruments using a non-parametric statistical approach (Mann-Whitney test). A comparative analytical design was conducted with 100 serum samples obtained via purposive sampling and divided for measurement with each device. Statistical analysis evaluated differences, and mean differences were calculated using the Hodges-Lehman method. Results showed mean cholesterol values of 182.98 mg/dL for Architect and 182.37 mg/dL for Alinity, with no significant difference (p=0.9942) and a median difference of 0.0 (95% CI: -9.0 to 9.0). Data distribution was nearly identical for both instruments in terms of mean and spread. Therefore, both methods demonstrate comparable validity in total cholesterol measurement, as they rely on similar principles and technologies, with reagents calibrated to the same standards.